Hubungan kemampuan berpikir kritis dan self regulated learning (srl) dengan tingkat literasi digital pada peserta didik kelas v sekolah dasar se-kecamatan laweyan - Puspitasari, Anindya; Matsuri, Matsuri; Ardiansyah, Roy (Universitas Sebelas Maret, 2023)
The aim of this research is to determine the relationship between critical thinking skills and Self Regulated Learning (SRL) with the digital literacy level of fifth grade elementary school students in Laweyan District. The research method used is quantitative. The sample for this research was 46 fifth grade students from 3 elementary schools in Laweyan District. The data collection techniques used are tests and scales. Data analysis uses prerequisite tests and hypothesis testing. The results of this research are that there is a simultaneous relationship between critical thinking and Self Regulated Learning (SRL) with the level of digital literacy which has a significance value of 0.000. The research explains that if critical thinking skills increase, SRL and also digital literacy levels will follow so that this research can be used as knowledge and reference for further research.